PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KUALITAS BACA AL-QUR’AN METODE TILAWATI DI MTS AL-MA’ARIF 02 SINGOSARI MALANG - Muhammad Yusuf Ahsani; Anwar Sa’dullah; Ika Anggraini (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Children are the next generation and are the backbone of the progress of the nation, state and religion in the future, therefore a child must be equipped with the ability to read the Qur'an. MTs Al-Ma'arif 02 Singosari Malang is one of the formal educations that will allow children to explore religious knowledge, especially about the ability to read the Qur'an. Through MTs Al-Ma'arif 02 Singosari Malang, a child can be educated with educators with a background in the basic Al-Qur'an tilawati method, in teaching reading the Qur'an to students. Teachers need a method to teach reading the Qur'an.Kata Kunci: Role, Islamic Religious Education Teacher, Quality of reading the Qur'an with the tilawati method